The Enforcement of Counter-Radicalism through Educational Values (Analytical analysis of the Book of I'tiqÄd by Al-BukhÄrÄ«) - Hanif Muhammad Kamil; Hudzaifah Achmad Qotadah; Iqbal Syafri (UIN Sunan Gunung Djati, 2020)
Radicalism is an understanding of social life, far beyond reconciliation and communication, similar to acts of violence. This misconception is indeed very dangerous, particularly if it is made in the name of religion itself. Evidently, the religious principle which always encourages a good and ethical way of life seems to have been misunderstood, perhaps abused. Radicalism might be handled and prevented by implementing the teachings of Imam al-BukhÄrÄ«, e.g. the I'tiqÄd, a clear understanding of religion and outstanding teaching practices. The aim of this research is to analyze the contents of the book upon its values of Islamic teachings concerning harmony through living together under a foundation of educational values towards radicalism. The research employed a full qualitative method and data documentation related to the research, which was then analyzed descriptively. In the meantime, the results of the study revealed that Imam al-BukhÄrÄ«, in his book I'tiqÄd al-BukhÄrÄ«, proposed four (4) educational values or elements of peace in Islamic teachings, namely: (1) harmony with the public at large, (2) harmony with the government, (3) tranquility with the Muslims, and (4) harmony with believers of other religions. These educational values could be an instructional approach for the enforcement of counter-radicalism that would be applicable to Islamic education in Indonesia.